Error-correcting codes with cryptographic algorithms - Popovska-Mitrovikj, Aleksandra; Markovski, Smile; Bakeva, Verica (IEEE, 2013)
Error-correcting codes based on quasigroups are defined elsewhere. These codes are a combination of cryptographic algorithms and error correcting codes. In a paper of ours we succeed to improve the speed of the decoding process by defining new algorithm for coding and decoding, named “cut-decoding algorithm”. Here, a new modification of the cut-decoding algorithm is considered in order to obtain further improvements of the code performances. We present several experimental results obtained with different decoding algorithms for these codes.
Keywords: bit-error probability, cryptcoding, errorcorrecting code, packet-error probability, quasigroup, quasigroup transformation, random code